Profession and Performance Aspects of oratory in the Greco-Roman world - Kremmydas, Christos; Powell, Jonathan; Rubinstein, Lene (Bulletin of the Institute of Classical Studies Supplements, 2013)
This volume brings together six papers relating to oratory and orators in public fora of Classical Greece and Rome. Edwards and Bers explore aspects of oratorical delivery in the Athenian courts and Assembly, including the demands placed on orators by the physical settings. Tempest examines the conceptions of oratorical competence and incompetence, particularly in respect of performance, as they are implied in Cicero.